2008
DOI: 10.1142/s0192415x08006296
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofCordyceps MilitarisSupplementation on Sperm Production, Sperm Motility and Hormones in Sprague-Dawley Rats

Abstract: Cordyceps species have been traditionally used as for the enhancement of sexual function, but its direct evidence is lacking. We investigated the spermatogenic effect of Cordyceps militaris (CM) as supplementation with CM mycelium to 7-week-old male Sprague-Dawley (SD) rats. Ninety rats (30 for each group) were selected to regular diet or diet supplemented with CM mycelium (1% and 5%) for 6 weeks. Epididymal sperm were collected from 6 animals per group at each interval of observation. They were allowed to rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 23 publications
3
30
0
1
Order By: Relevance
“…It was reported that the sperm production is enhanced significantly by supplementation with CM mycelium even to the subfertile adult pigs (Lin et al,2007). Our present result was in agreement with previous reports (Hsu et al, 2003;Huang et al, 2004;Chang et al, 2008).…”
Section: Change Of Testosterone Concentrationssupporting
confidence: 94%
See 1 more Smart Citation
“…It was reported that the sperm production is enhanced significantly by supplementation with CM mycelium even to the subfertile adult pigs (Lin et al,2007). Our present result was in agreement with previous reports (Hsu et al, 2003;Huang et al, 2004;Chang et al, 2008).…”
Section: Change Of Testosterone Concentrationssupporting
confidence: 94%
“…There was no difference in bodyweight in rats before, during and after the experiment among rats between the treatment group and the control group (Table 1). Chang et al (2008) reported that change of body weights in rats fed with CM supplementation was not observed.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown to enhance sexual function. 8 It has been used in the treatment of chronic bronchitis, asthma, and chronic renal failure. Cordycepin (3´-deoxyadenosine) is the main functional component of Cordyceps militaris.…”
Section: Introductionmentioning
confidence: 99%
“…Uno de los componentes bioactivos más importantes del Cordyceps es la cordicepina. Posee un efecto modulador inmunológico y antiinflamatorio que mejora el estado energético de la célula y elimina los radicales libres de oxígeno 36 .…”
Section: Tratamiento Del Grupo De Estudiounclassified